SISTEM SPASIAL PENGELOLAAN SAMPAH PERMUKIMAN BERBASIS MASYARAKAT (BANK SAMPAH) DI KOTA YOGYAKARTA - Carina Sarasati; Edward Endrianto Pandelaki; Suzanna Ratih Sari (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2018)
Abstract:. The city of Yogyakarta has a waste problem where there is an imbalance between the amount of waste generated and waste management space. Therefore, community-based waste management was appear in the form of ”Garbage Bank” which expected to manage the inorganic waste at RW level. The existence of the “Garbage Bank” is supported by the Mayor of Yogyakarta program and also some policies of the Central and Regional Governments. However, in reality there is no spatial system of waste management of settlements which clear and integrated through